Dietary Histamine Impairs the Digestive Physiology Function and Muscle Quality of Hybrid Grouper (Epinephelus fuscoguttatus♀ × Epinephelus lanceolatus♂) - Yumeng Zhang; Hang Zhou; Yu Liu; Lulu Zhu; Jiongting Fan; Huajing Huang; Wen Jiang; Junming Deng; Beiping Tan (MDPI AG, 2023)
An 8-week feeding experiment was conducted to investigate the effect of dietary histamine on growth performance, digestive physiology function and muscle quality in a hybrid grouper (Epinephelus fuscoguttatus♀ × Epinephelus lanceolatus♂). Seven isoproteic (50%) and isolipidic (11%) diets were prepared with various histamine inclusion levels of 0, 30, 60, 120, 240, 480 and 960 mg/kg in diets (actual contents were 72.33, 99.56, 138.60, 225.35, 404.12, 662.12 and 1245.38 mg/kg), respectively. Each diet was randomly assigned to triplicates of 30 juveniles (average body weight 14.78 g) per tank in a flow-through mariculture system. The increase in the dietary histamine level up to 1245.38 mg/kg made no significant difference on the growth rate and feed utilization of the grouper. However, the increased histamine content linearly decreased the activities of digestive enzymes, while no differences were observed in groups with low levels of histamine (≤404.12 mg/kg). Similarly, high levels of histamine (≥404.12 mg/kg) significantly damaged the gastric and intestinal mucosa, disrupted the intestinal tight junction structure, and raised the serum diamine oxidase activity and endotoxin level. Meanwhile, high doses of histamine (≥662.12 mg/kg) significantly reduced the activities of antioxidant enzymes, upregulated the relative expression of Kelch-like ECH-associated protein 1, and hardened and yellowed the dorsal muscle of grouper. These results showed that dietary histamine was detrimental to the digestive physiology function and muscle quality of the grouper, although it did compromise its growth performance.